Filsafat Sufisme: Pemikiran Jalaluddin Rumi dan Relevansinya di Dunia Modern - Aulia, Intan; S, Sulistiani; Munthe, Ratna Sari; Wahyuni, Ridzky; Siregar, Raja Syahnan Habiaran; Rambe, Rizki Dharmawan; Hutapea, Boni Tarsan; Harahap, Salahuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The philosophy of Sufism is a school of thought that focuses on achieving closeness to God through inner experience. This study aims to explore the thoughts of Jalaluddin Rumi, a great figure in Sufism, and analyze its relevance in the context of the modern world. The research method used is a literature review by studying Rumi's works and literature related to Sufism. The results of the study show that Rumi's thoughts on love, unity, and spiritual journey are very relevant to the challenges of modern life, such as the search for the meaning of life and inner peace. The conclusion of this study is that the philosophy of Sufism, especially that expressed by Rumi, can provide deep insight and enlightenment for individuals who are seeking peace and closeness to God in this materialistic world.